The Relationship Between Smoking Behavior And Respiratory Health Disorders - Yona Sahalessy; Rahmat Pannyiwi; Ayu Sunarti. S; Elvira Safidni; Andi Ernawati Manuntungi (International Journal of Health Sciences, 2026)
Smoking is a major risk factor for respiratory health problems. The harmful substances in cigarettes, such as nicotine, tar, and carbon monoxide, can cause respiratory tract irritation, decreased lung function, and increased the risk of chronic respiratory diseases. This study aims to determine the relationship between smoking behavior and respiratory health problems. The study used an observational analytical design with a cross-sectional approach. The study sample consisted of 100 respondents selected using a purposive sampling technique. Data were collected through a smoking behavior questionnaire and a respiratory complaints questionnaire. Data analysis was performed using the Chi- Square test. The results showed a significant relationship between smoking behavior and respiratory health problems (p < 0.05). It was concluded that smoking behavior is closely related to an increased risk of respiratory health problems.